Jumlah Sel Neuron Cerebrum pada Paparan Musik Mozart Lebih Tinggi Dibandingkan Dengan Paparan Musik Indonesia - Agustina Mar'atus Sholichah; Hermanto Tri Joewono; Widjiati Widjiati (FORIKES, 2020)
Background: Intelligence management can produce superior human resources with integrated brain. Mozart music stimulus during pregnancy has been shown to increase the number of neuron of the fetal brain. The study of pop and religious music needs to be improve because they are more popular in Indonesia. Objective: To analyze the differences of number of Neuron in the Cerebrum Rattus norvegicusoffspring that exposed to Mozart, Indonesian pop music and Indonesian religious music during pregnancy. Methods: An experimental study with a post-test only control group design. Groups divide into treatment music groups: Mozart, pop and religious. Treatment in a soundproof room for 1 hour, starting the 10th-day of pregnancy, intensity of 65 dB with a distance of 25 cm from the cage. The number of neuron was counted from HE brain preparations of the head Rattus norvegicusoffspring and analyzed using appropriate statistics test. Results: There were significant differences in the number of neuron of Rattus norvegicusoffspring in cerebrum between groups with p = 0,000 (mean Mozart music group 28.14 ± 3.02, Indonesian pop music 19.71 ± 1.80, Indonesian religious music 24.14 ± 2.91) and Mozart gave a higher number of neuron than Indonesia religious music and Indonesian pop music. Conclusion: Mozart music gave a higher number of neuron in the Cerebrum than Indonesian religious music and Indonesian pop music. Keywords: neuron; cerebrum; Mozart music; Indonesian music ABSTRAK Latar belakang: Pengelolaan kecerdasan otak yang terintegrasi akan menghasilkan SDM yang unggul. Stimulus musik Mozart selama kehamilan terbukti meningkatkan jumlah sel neuron di otak janin. Musik pop dan religi perlu dilakukan penelitian karena lebih populer di Indonesia. Tujuan: Menganalisis perbedaan jumlah sel neuron di Cerebrum Rattus norvegicusbaru lahir antara yang mendapat paparan musik Mozart, musik pop Indonesia dan musik religi Indonesia selama kebuntingan. Metode: Studi eksperimental dengan desain post test only control group. Kelompok perlakuan dibagi menjadi kelompok musik Mozart, musik pop Indonesia dan musik religi Indonesia. Perlakuan di ruang kedap suara selama 1 jam pada malam hari mulai hari ke-10 kebuntingan, intensitas 65 dB dengan jarak 25 cm antara kandang dan speaker. Jumlah sel neuron dihitung dari preparat pewarnaan Hematoxylin-Eosin otak anak Rattus norvegicusdan dianalisis dengan statistik yang sesuai. Hasil: Terdapat perbedaan yang signifikan pada jumlah sel neuron cerebrum Rattus norvegicus baru lahir antar kelompok dengan nilai p=0,000 (rerata kelompok musik Mozart 28,14±3,02, musik pop Indonesia 19,71±1,80 dan musik religi Indonesia 24,14±2,91) dan musik Mozart memiliki jumlah sel neuron lebih tinggi daripada musik religi Indonesia dan musik pop Indonesia. Kesimpulan: Kelompok musik Mozart memiliki jumlah sel neuron di cerebrum yang lebih tinggi dibandingkan kelompok musik Indonesia. Kata kunci: neuron; cerebrum; musik Mozart; musik Indonesia